Buddhist Temple Networks in Medieval Japan: Daigoji, Mt. Kōya, and the Miwa Lineage - Andreeva, Anna (Japanese journal of religious studies, 2020)
The intellectual links between medieval esoteric temples and localized Shingon movements are still far from being well understood. Although a part of education at major monastic complexes such as Daigoji and Mt. Kōya, transmissions of esoteric theories were not uniform and varied depending on their recipients’ social status. A comparative reading of the Yugikyō transmissions imparted by the abbot Jikken of Kongōōin to his official disciple Dōhan and a lesser-known semi-itinerant priest, Rendōbō Hōkyō, from a local training hall at Mt. Miwa in Nara Prefecture shows that during the late twelfth to fourteenth centuries non-elite practitioners in medieval Japan, such as those associated with the local Miwa lineage, did not simply study the Yugikyō teachings but were actively involved in their dissemination. They used theories associated with this sutra as key parts of their own religious capital and transported them from large esoteric temples further afield to Japan’s countryside.